Tolerância do campim marandu a doses de manganês - Guirra, Ana Paula Pires Maciel [UNESP]; Fiorentin, Ciro Franco [UNESP]; Prado, Renato de Mello [UNESP]; Caetano, Mayra Cristina Teixeira [UNESP]; Felici, Ana Claudia [UNESP] (My University, 2011)
The cultivation of pastures in Brazil is mostly done with the species Brachiaria spp. However, there is little research on nutrition with manganese for this forage. It was aimed to asses the effects of manganese in the development and nutrition of marandu grass. The experimental design used was fully randomized, consisting of five rates of manganese (0, 15, 30, 60 e 120 mg dm -3) and four repetitions. The experimental unit was formed in a vase filled with a Red Latosol dystrophic. There were two cuts, the first after 38 days of transplanting seedling and the second 30 days after the first cut. Was evaluated the content of manganese leaf, the dry mass of the shoot, the number of tillers and the leaf area. The levels of manganese increased its accumulation in the plant, second cut compared to the first cut. The marandu grass showed high tolerance to manganese toxicity, reaching a high leaf content in the shoot without affecting plant growth.
Tolerance of marandu grass to doses of manganese
Keywords: Brachiaria brizantha; Fertility; Micronutrient; Nutrition; Pasture